Effectiveness of the Index Card Match (ICM) Method in Improving Science Learning Outcomes of Student at Ban Eyoh School Thailand - Heni Mulyani Pohan; Fatma Suryani Harahap; Hotrina Sitompul; Jalilah Azizah Lubis; Nur Sahara (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the effectiveness of applying the Index Card Match (ICM) method in improving science learning outcomes of students at Ban Eyoh School in Thailand. This study uses a quantitative experimental research design with a Quasi-Experimental Design approach. Data were collected through pretest and posttest administered before and after the implementation of the ICM method. Statistical analysis showed a significant difference between the experimental and control classes, with a sig. value of 0.001 (< 0.05). The average posttest score of the experimental (80.61) was 10.31 points higher than that of the control (70.30). This effectiveness was reinforced by the N-Gain Score of “quite effective” (56%) for ICM, while the control class was “ineffective” (39%). The effectiveness of the ICM learning model is also demonstrated by: 1) A statistically significant difference between the learning outcomes of the experimental group (ICM) and the control group (conventional), 2) A higher posttest average score for the experimental group compared to the control group, and 3) The learning effectiveness level (N-Gain Score) in the experimental class was categorized as “quite effective”, while the control class was “ineffective”. Therefore, ICM can be recommended as an alternative innovative learning model, especially in the context of science learning in a challenging